2014
DOI: 10.2169/internalmedicine.53.1316
|View full text |Cite
|
Sign up to set email alerts
|

Response to Clopidogrel and Its Association with Chronic Kidney Disease in Noncardiogenic Ischemic Stroke Patients

Abstract: Objective Noncardiogenic ischemic stroke patients with chronic kidney disease (CKD) are known to have a greater rate of ischemic stroke recurrence than those without. Although clopidogrel is often used to prevent the recurrence of noncardiogenic ischemic stroke, the relationship between the response to clopidogrel and CKD is unclear. In the present study, the relationship between the response to clopidogrel and the presence of CKD was investigated in noncardiogenic ischemic stroke patients. Methods A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In earlier studies, we measured platelet aggregation in non-cardiogenic ischemic stroke patients and found that 8-29% showed clopidogrel resistance (7,8). Various factors have been identified as causing individual variability in the antiplatelet effect of clopidogrel, including genetic polymorphism of cytochrome P450 (CYP) enzymes (9,10), and our group reported the involvement of chronic kidney disease (11). However, little is known regarding whether a relationship exists between smoking and the antiplatelet effect of clopidogrel in non-cardiogenic ischemic stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier studies, we measured platelet aggregation in non-cardiogenic ischemic stroke patients and found that 8-29% showed clopidogrel resistance (7,8). Various factors have been identified as causing individual variability in the antiplatelet effect of clopidogrel, including genetic polymorphism of cytochrome P450 (CYP) enzymes (9,10), and our group reported the involvement of chronic kidney disease (11). However, little is known regarding whether a relationship exists between smoking and the antiplatelet effect of clopidogrel in non-cardiogenic ischemic stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…Continued previous population-based study. 35,36 In cases of platelet responsiveness to aspirin, the degree of responsiveness can affect clinical outcome, stroke severity, and ischemic lesion volume. 35 Finally, we did not experimentally evaluate antiplatelet response (i.e., determine aspirin or clopidogrel resistance as a laboratory phenomenon through ex vivo tests).…”
mentioning
confidence: 99%
“…Among affective factors correlated with clopidogrel response, the cytochrome P-450 enzyme was established to be the most important factor, correlated with genetic factors 2) . In addition, some studies have reported that drugs which are metabolized by the cytochrome P-450 enzyme, such as statins, PPIs, CCBs, β-blockers and/or SSRIs, affect clopidogrel response, as well as patient clinical factors such as DM, renal failure, and/or BMI 7 , 15 , 18 , 19 , 30) . In our study, pre-PRU and serum platelet count were important predictive factors, as in other studies 10) .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data consisted of age, sex, diabetes mellitus (DM) status, blood pressure, history of smoking, alcohol use, history of stroke, history of heart disease, and body mass index (BMI). Laboratory data consisted of glomerular filtration rate, platelet count, cholesterol levels, triglyceride levels, high-density lipoprotein levels, and low-density lipoprotein levels 7 , 15 , 18 , 21) . These factors were defined as follows : DM and hypertension (HTN) were defined by medical treatment after diagnosis, patients were considered smokers only if they currently smoked, alcoholism was defined as the consumption of more than 14 standard drinks per week or four drinks per day, history of stroke was determined by a previous cerebral infarction or intracranial hemorrhage, and history of heart disease included myocardial infarction, angina, valve disease, congenital heart disease, or previous heart operations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation